Environmental selection overturns the decay relationship of soil prokaryotic community over geographic distance across grassland biotas - Zhang, Biao; Xue, Kai; Zhou, Shutong; Wang, Kui; Liu, Wenjing; Xu, Cong; Cui, Lizhen; Li, Linfeng; Ran, Qinwei; Wang, Zongsong; Hu, Ronghai; Hao, Yanbin; et al. (eLife, 2022)
Though being fundamental to global diversity distribution, little is known about the geographic pattern of soil microorganisms across different biotas on a large scale. Here, we investigated soil prokaryotic communities from Chinese northern grasslands on a scale up to 4000 km in both alpine and temperate biotas. Prokaryotic similarities increased over geographic distance after tipping points of 1760–1920 km, generating a significant U-shape pattern. Such pattern was likely due to decreased disparities in environmental heterogeneity over geographic distance when across biotas, supported by three lines of evidences: (1) prokaryotic similarities still decreased with the environmental distance, (2) environmental selection dominated prokaryotic assembly, and (3) short-term environmental heterogeneity followed the U-shape pattern spatially, especially attributed to dissolved nutrients. In sum, these results demonstrate that environmental selection overwhelmed the geographic ‘distance’ effect when across biotas, overturning the previously well-accepted geographic pattern for microbes on a large scale.
Keywords: prokaryote; distance-decay; U-shape; grassland; biota; microbial community